Revalidation of Caridina natalensis De Man, 1908 (Crustacea: Decapoda: Atyidae) in the South Western Indian Ocean - de Mazancourt, Valentin; Castelin, Magalie; Renneville, Clementine; Mlambo, Musa C.; Marquet, Gerard; Keith, Philippe (Zootaxa, 2019)
Numerous specimens of a freshwater shrimp with small eggs belonging to the Caridina nilotica complex collected in the South Western Indian Ocean were studied and compared with recent and old collection specimens genetically (16S mitochondrial analysis for recent and type specimens) and morphologically. The results revealed that, in the Indian Ocean, what has been identified by several authors under various species names of the complex C. nilotica, was in fact C. natalensis De Man, 1908. This valid species is re-described and compared with closely related species, often confused with it in this area: C. brachydactyla De Man, 1908, C. brevidactyla Roux, 1920, C. gracilipes De Man, 1892 and C. longirostris H. Milne Edwards, 1837.